PENDIDIKAN KELUARGA BERBASIS GENDER PERSPEKTIF IBU NYAI DI MADURA - Mahmud, Amir; Muawaroh, Mundiro Lailatul; Abdullah (AL - IBRAH, 2025)
The role of the family is very important in shaping the development of a child's personality, especially as parents have a big influence, where they act as educators above all else. The family is the first center of education. It is in this family that children are first educated and guided. Family education is very important education, especially Islamic education which must be provided by both parents from early childhood until adulthood. Apart from that, the family also functions as a basis for forming a child's personality. Therefore, the success of education in the family must be supported by a pleasant atmosphere on the part of the family or parents themselves, as well as the child's environment and social friends. In gender education, parents have a very important role in raising and directing their children. The purpose of this research is: To explain the views of Mrs. Nyai in Madura regarding parental justice towards all children in providing education. In this research the author used qualitative and quantitative methods, data collection techniques using observation, interviews, documentation methods. The results of the research show that Nyai mothers in Madura must carry out the responsibility of educating their children for their parents. Because they believe that children are a God-given responsibility to be educated and taught. Nyai's view of the Madura Islamic Boarding School concerns the example that must be set by both parents, on the grounds that parents must be able to be role models and role models for their sons and daughters. Mothers are role models who are always imitated and imitated by their children in managing their lives. In the field of education, also for them, every child has the same right to be educated in the family, so that justice for parents in educating their children is a must.